Terapi Bekam (Hijamah) dalam Perspektif Islam dan Medis - Hidayat, Hakmi; Amiruddin, Muhammad; Aktifa, Ana Fadilia; Haryadi, Mahardika Chory; Azzahra, Nabila (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 2 (2022): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2022)
Muslims have the holy book Al-Quran and Hadith as the main source of law in various issues, including health. One of the medical therapies mentioned in the Al-Qur'an and Hadith is cupping, which removes dirty blood from the body through a wound process carried out on the surface of the skin. This study aims to discover the history of cupping until it becomes a form of health therapy as well as views from the Islamic and medical side of cupping therapy. The method used is a literature study. Cupping therapy has existed since ancient Egypt and developed in various civilizations in various countries in the world, from Egypt, China, Europe, and America. The law of cupping in Islam is permissible and has been found in the books of nine hadith figures, special discussion of cupping is mentioned 275 times. The Prophet SAW recommended cupping in the middle of the month or after the middle of the month, but it is customary to do it in the third week. Cupping therapy in the medical world is explained using the approach of traditional medicine and modern medicine. Both agree that cupping therapy at certain points in the body can cure several diseases where the cupping is done or far from the area where the cupping is done. The benefits of cupping from a medical point of view are curing local ailments (neck pain, back pain, shoulder pain, knee pain, headaches, and migraines) and systematic diseases (Diabetes mellitus, hypertension, rheumatoid arthritis). In cupping therapy, it is mandatory to carry out infection control (washing hands before starting therapy, wearing complete PPE, disinfecting the skin and the place of therapy, managing waste, and trying to use disposable therapy equipment).